Three Worlds of Professional and Managerial Staff in France - Thoemmes, Jens (Relations industrielles / Industrial Relations, 2016)
SummaryChanges in the work of professional and managerial staff (PMS, cadres) in France were studied in a research project based on 100 interviews, conducted in seven private and public companies. Through a discourse and correspondence analysis—of a corpus amounting to some 600,000 words—, this study concludes that this particular French employment group can be seen neither as a homogeneous entity, nor as a totally fragmented socio-professional category. Rather, reflecting on working life experiences, it describes three groups that correspond to a horizontal division of professional and managerial staff: the serene, the individualized and the resistant.“Serene” PMS perceive their professional lives as being free of major problems. Their career trajectories go up, leading to senior positions in the organization. Training opportunities are used and personal assessment by supervisors is seen as a favourable orientation. This world is stabilized by law or by collectively negotiated agreements and characterized by autonomy and concern for the common good, which are the basis of their beliefs.“Individualized” PMS consider themselves to be responsible for their own success and to be the architects of their careers. They put in countless hours of service, arriving early in the morning and going home late in the evening. They prioritize work over family and aim to be active in highly competitive markets. The individualized have everything they need to be “happy,” except that work leaves them very little time for their private lives. In addition, these employees fear threats to job security and to their careers.“Resistant” PMS’s working time is measured in hours and minutes. Unpaid overtime is refused. This strict regulation of working time is nevertheless accompanied by a considerable workload. Deadlines are difficult to respect. Manifestations of stress and responsibilities in personnel management lead the resisting employee to a negative view of work. The importance of sociability in and outside of work compensates for the loss of the traditional prestige of these PMS. // Les changements dans le travail des professionnels et du management (cadres) en France ont été étudiés dans le cadre d’un projet de recherche sur la base de 100 entretiens, menés dans sept entreprises privées et publiques. Une analyse du discours et une analyse factorielle des correspondances basée sur un corpus de 600 000 mots montre que cette catégorie professionnelle ne peut être considérée ni comme une entité homogène, ni comme totalement fragmenté. En partant des expériences de vie au travail des employés, nous décrivons trois groupes, correspondant à une division horizontale des cadres : les sereins, les individualisés et les résistants.Les « sereins » perçoivent leur vie professionnelle comme étant exempt de problèmes majeurs. Leur trajectoire de carrière est montante, conduisant à des postes de direction dans l’organisation. Les possibilités de formation sont pleinement utilisées et l’évaluation personnelle par les superviseurs est considérée avec bienveillance. Ce monde est stabilisé par la loi ou par des accords négociés collectivement. Il est caractérisé par l’autonomie et par le souci du bien commun, qui sont la base de leurs croyances.Les « individualisés » se considèrent responsables de leur propre succès et ils estiment être les architectes de leur carrière. Ils consacrent d’innombrables heures de service, en arrivant tôt le matin et en rentrant à la maison tard dans la soirée. Ils privilégient le travail à la famille et voudraient être actifs dans des marchés hautement concurrentiels. Les individualisés ont tout pour être « heureux », sauf que le travail ne leur laisse que très peu de temps pour leur vie privée. En outre, ces employés craignent les menaces sur la sécurité de leur emploi et de leur carrière.Le temps de travail des « résistants » se mesure en heures et minutes. Des heures supplémentaires non rémunérées sont refusées. Cette règlementation stricte du temps de travail est néanmoins accompagnée d’une charge de travail considérable. Les délais sont difficiles à respecter. Les manifestations de stress et les responsabilités dans la gestion du personnel conduisent les résistants à une vision négative du travail. L’importance de la sociabilité dans et en dehors du travail compense ici la perte du prestige traditionnel des cadres.